Enhanced Chemical Reactivity of Pristine Graphene Interacting Strongly with a Substrate: Chemisorbed Carbon Monoxide on Graphene/Nickel(1 1 1). Issue 15 (19th June 2015) - Smerieri, Marco; Celasco, Edvige; Carraro, Giovanni; Lusuan, Angelique; Pal, Jagriti; Bracco, Gianangelo; Rocca, Mario; Savio, Letizia; Vattuone, Luca
Abstract Graphene is usually considered a chemically inert material. Theoretical studies of CO adsorption on free‐standing graphene predict quite low adsorption energies (<0.1 eV). However, we show here by vibrational spectroscopy and scanning tunneling microscopy that the nondissociative chemisorption of CO occurs at cold, pristine graphene grown on Ni(1 1 1). The CO adlayer remains stable up to 125 K, although some coverage survives flashes to 225 K. This unexpected result is explained qualitatively by the modification of the density of states close to the Fermi energy induced by the relatively strong graphene–substrate interaction. The value of the adsorption energy allows us to estimate an equilibrium coverage of the order of 0.1 monolayers at 10 mbar pressure, which thus paves the way for the use of graphene as a catalytically active support under realistic conditions.